Evaluating Knowledge and Attitudes Toward Antibiotic Use Among Pharmacy Students at Three Universities in Bali - I Gusti Ayu Rai Widowati; Ni Putu Rizky Sukmayanti; Putu Ayu Laksmini (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2024)
Antimicrobial resistance poses a significant threat to global health, making the understanding of antibiotic use among healthcare students critical. This study aimed to assess the knowledge, attitudes, and practices regarding antibiotic use among pharmacy students in Bali. A quantitative descriptive approach with a cross-sectional design was employed, involving 105 pharmacy students. Data were collected through a questionnaire distributed via Google Forms and analyzed using SPSS version 15.0. The findings indicated that most of the respondents were aged 19-24 years (96.2%), predominantly female (85.7%), and enrolled in undergraduate programs (77.1%). A substantial proportion (84.8%) obtained antibiotics with a doctor's prescription, while health workers served as the primary source of information for self-treatment (74.3%). Amoxicillin emerged as the most commonly used antibiotic (71.4%), with fever being the most reported complaint (55.2%). The questionnaire results revealed high levels of knowledge (41.9%), a positive attitude towards antibiotic use (94.3%), and good practice (99.0%) among pharmacy students. Statistical analysis showed a significant relationship between knowledge and attitudes toward antibiotic use practices, with r = 0.306 (p = 0.001). Additionally, the correlation between attitudes and practices was stronger, with r = 0.385 (p < 0.000). The study concludes that pharmacy students in Bali exhibit a high level of knowledge and a positive attitude toward antibiotic use, which correlates significantly with their practices. However, the study underscores the need for continuous education on responsible antibiotic use to combat antimicrobial resistance effectively.